Initiation and elongation of mammalian mitochondrial protein synthesis - Spremulli, Linda L. (Henry Stewart Talks, 2018)
General features of mammalian mitochondrial translation: the genetic code, tRNAs, mRNAs and ribosomes, Initiation of translation: current working model, properties of the initiation factors, Elongation of translation: current working model, properties of the elongation factors, Role of the membrane and possible translational activators, Major remaining questions